Abnormal uterine bleeding; its prevalence, causes and management in a tertiary care hospital - Shabir Ahmed Choudhury; Pranoy Nath (Barpeta Obstetrics and Gynaecological Society, 2020)
Objectives: To study the prevalence, causes and management of abnormal uterine bleeding (AUB) in Silchar Medical College and Hospital, Silchar. Methods: It was an observational study conducted in the Department of Obstetrics and Gynaecology, Silchar Medical College, Silchar from June 5th of 2018 to June 4th of 2019. Results: Prevalence of AUB was found to be 20.48%. The age-group presenting with AUB, most commonly was in between 41 to 45 years of age (46%), and the most common histological pattern was proliferative (42%). Heavy menstrual bleeding (menorrhagia) was found to be the most common problem in AUB patients (58.45%). As per PALM-COEIN classification, the most common type in our study was found to be AUB-L (30%). In this study, most common treatment/surgery in AUB patients done is hysterectomy (47%). Conclusion: Prevalence and pattern of AUB varies according to the age and parity of the patient. Specific diagnosis to rule out the cause of AUB and proper management in early stages will help to reduce patient's morbidity. After proper classification of AUB by PALM-COEIN, patients can be treated medically or surgically according to the cause leading to better success rate.